Conditioning and sprinting technique - Strojnik, V. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this paper was to show relationship between muscle strength and sprinting technique. Stride length and frequency correspond to different kinetic chains and by changing their characteristics the stride pattern will change as well. Ground reaction force parameters of squat jump may be used for functional assessment of kinetic chain due to its proximal-distal pattern of muscle activation. The first part of squat jump is dominated by hip extensors (proximal part) while final take-off velocity is related to knee extensors (distal part). Since grabbing is performed by hip extensors, stride frequency is expected to be related to the first part of the squat jump. Pushing is mainly performed by knee extensors and thus provides rationale for relation between stride length and take-off velocity.